Jawabanmu

2014-09-07T19:39:41+07:00
1. (7x - 6y + 8) + (-3 + xy -4 )
     = 7x - 6y + 8 + (-3) + xy - 4
     = 7x -6y + xy + 1
2. a.  (-25p + 9p) dari (10p + 5q)
           = 10p + 5q - (-25p + 9p)
           = 10p + 5q + 25p + 9p
           = 35p - 5q
     b.  -7x(y + 2) dari -4xy(2x +9)
            = -7xy - 14x dari -8x²y - 36xy
            = -8x²y - 36xy - (-7xy - 14x)
            = -8x²y - 36xy  + 7xy + 14x
            = -8x²y - 43xy + 14x
 
    
soal nomor 2.a ini (-25p + 9q) dari (10p + 5q)
9q yah, bukan 9p